Hypothalamic Agouti‐Related Peptide mRNA is Elevated During Natural and Stress‐Induced Anorexia. (September 2015) - Dunn, I. C.; Wilson, P. W.; D'Eath, R. B.; Boswell, T.
<x xml:space="preserve">Abstract</x> As part of their natural lives, animals can undergo periods of voluntarily reduced food intake and body weight (i.e. animal anorexias) that are beneficial for survival or breeding, such as during territorial behaviour, hibernation, migration and incubation of eggs. For incubation, a change in the defended level of body weight or 'sliding set point' appears to be involved, although the neural mechanisms reponsible for this are unknown. We investigated how neuropeptide gene expression in the arcuate nucleus of the domestic chicken responded to a 60–70% voluntary reduction in food intake measured both after incubation and after an environmental stressor involving transfer to unfamiliar housing. We hypothesised that gene expression would not change in these circumstances because the reduced food intake and body weight represented a defended level in birds with free access to food. Unexpectedly, we observed increased gene expression of the orexigenic peptide agouti‐related peptide (AgRP) in both incubating and transferred animals compared to controls. Also pro‐opiomelanocortin (POMC) mRNA was higher in incubating hens and significantly increased 6 days after exposure to the stressor. Conversely expression of neuropeptide Y and cocaine‐ and amphetamine‐regulated transcript gene was unchanged in both experimental situations. We conclude that AgRP expression remains sensitive to the level of energy stores during natural anorexias, which is of adaptive advantage, although its normal orexigenic effects are over‐ridden by inhibitory signals. In the case of stress‐induced anorexia, increased POMC may contribute to this inhibitory role, whereas, for incubation, reduced feeding may also be associated with increased expression in the hypothalamus of the anorexigenic peptide vasoactive intestinal peptide.